تطويْر الوسائِل المتَعدِّدة باسْتخدَام ماكرُوميديا فلاش في تدريْب اختِبار معْيار الكفاءَة في اللغَة العربيَّ - Ramdhan Yurianto (IAI Muhammadiyah Sinjai, 2022)
This research aims to develop the Arabic interactive multimedia for training test of Arabic language ability standard / اخْتِبَار مِعْيار الكَفَاءَة فِي اللُّغَة العَرَبِيَّة (IMKA) and to test its validity, practicality and effectiveness for students of Walisongo Islamic State University Semarang. Because of difficulty of Arabic language standard test, the high cost of teaching privately, and no material and means to teach the Arabic language proficiency standard test than 92% of the students demanding to train the Arabic test by audio-visual application. The type of this research is research and development (R&D) using Borg and Gall model by using the multistage random sampling technique for 24 students. This development produces the application for teaching the Arabic language in the form of interactive multimedia with the extension of .exe. In terms of validity, these applications find a percentage of 84% (multimedia validator expert) and 75% (material validator expert) with a sufficiently correct category, and they should be slightly revised. In terms of practicality, these ap-plications find the rating rate of 4.5 out of the top rating 5 in their class as very good and practical to use. In terms of effectiveness, these applications find Normalized Gain 0.38 of the highest grade 1 in the medium class and effective for use.